Strategy to Improve Student’s Achievement in Science at Madrasah with Islamic Boarding School (Pesantren) whose Qur'an Memorization Program - Choeroni, Choeroni; Anwar, Khoirul; Nugroho, Bekti Taufiq Ari (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2024)
The focus of learning in natural science at Madrasah has not received serious treatment by teachers and stakeholders of madrasah both in private and public madrasah, especially Madrasah with Islamic Boarding School (Pesantren) whose Qur'an Memorization Program, resulting in the scientific achievements of the students are not so satisfying. This study aims to provide an overview of the implementation of the achievement clinic strategy and its effect on the improvement of students’ scientific achievements in excellent Madrasah with Islamic Boarding School (Pesantren) which has Qur'an Memorization Program in Kudus, Indonesia. The method used in this study is field research with a descriptive qualitative approach analysis. The data sources were from religion teachers, science teachers, research teachers, and science laboratory superintendents and students. Data collected include observations, interviews, and documentation. Furthermore, the data analysis technique covered six steps, such as preparing and processing data, reading the entire data, coding all the data, describing the type of data, presenting the data, and analyzing the data. The results showed that the implementation of the achievement clinic was carried out by using several steps: (1) the integration of science and religion learning; (2) the addition of research courses; (3) conducting structured and scheduled mentoring; (4) intensive deepening activity before the competition; and (5) complete learning and research infrastructure. The result shows that the achievement clinic strategy can increase the students' ability in science and lead, as well as enable several students to win science olympiads both at the national and international levels